PENGARUH MODEL PEMBELAJARAN TAKE AND GIVE DALAM MENINGKATKAN HASIL BELAJAR SISWA - Hastuti Diah Ikawati (Jurnal Paedagogy, 2017)
The research objective was to determine the effect of the take and give type of cooperative learning model on student achievement in ICT class IX subjects at Janapria Junior High School. This type of research is a pure experiment with a one group pretest – postest design, that is, a research design carried out in one group only without a comparison group. The population in this study were all students of class IX at Janapria Junior High School, amounting to 74 students, while the sample of this study was 25 students of class IXB. The researcher used simple random sampling, which is a lottery system with the intention that each class has the same opportunity to become a member of the sample in this study. The data collection method used in this study was the test method as the main method and the method of documentation and the interview method as a complementary method, while the data analysis used the t-test. The result of this research is 5,759 and after being consulted with t table on d.f 24 with a significance level of 5%, which is 2.064. Based on these results, then tcount> ttable (5.759> 2.064) proves that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted which reads: There is an effect of the take and give type of cooperative learning model on student achievement in classroom ICT subjects. IX at Janapria Junior High School.